Longitudinal changes in macular retinal layer thickness in pediatric populations: Myopic vs non-myopic eyes. - Scott A Read; David Alonso-Caneiro; Stephen J Vincent (PLoS ONE)
Knowledge of the normal in vivo thickness of the retina, and its individual layers in pediatric populations is important for diagnosing and monitoring retinal disorders, and for understanding the eye's normal development and the impact of eye growth and refractive error such as myopia (short-sightedness) upon retinal morphology. In this prospective, observational longitudinal study, total retinal thickness (and individual retinal layer thickness) and the changes in retinal morphology occurring over an 18-month period were examined in 101 children with a range of refractive errors. In childhood, the presence of myopia was associated with subtle but statistically significant (p<0.05) changes in the topographical thickness distribution of macular retinal thickness (and retinal layer thickness), characterised by a thinning of the parafoveal retina (and parafoveal or perifoveal thinning in most outer and inner retinal layers). The parafoveal retina was on average 6 μm thinner in myopic children. However, over 18 months, longitudinal changes in retinal thickness and individual layers were of small magnitude (average changes of less than 2 μm over 18 months), indicative of a high degree of stability in retinal morphology in healthy adolescent eyes, despite significant eye growth over this same period of time. This provides the first detailed longitudinal assessment of macula retinal layer morphology in adolescence, and delivers new normative data on expected changes in retinal structure over time and associated with myopia during this period of childhood development.